Downlink Coexistence Performance Assessment and Techniques for WiMAX Services from High Altitude Platform and Terrestrial Deployments. (21st September 2008) - Yang, Z.; Mohammed, A.; Hult, T.; Grace, D.
Abstract : We investigate the performance and coexistence techniques for worldwide interoperability for microwave access (WiMAX) delivered from high altitude platforms (HAPs) and terrestrial systems in shared 3.5 GHz frequency bands. The paper shows that it is possible to provide WiMAX services from individual HAP systems. The coexistence performance is evaluated by appropriate choice of parameters, which include the HAP deployment spacing radius, directive antenna beamwidths based on adopted antenna models for HAPs and receivers. Illustrations and comparisons of coexistence techniques, for example, varying the antenna pointing offset, transmitting and receiving antenna beamwidth, demonstrate efficient ways to enhance the HAP system performance while effectively coexisting with terrestrial WiMAX systems.